The use of aesthetic medicine in the treatment of rosacea - Latała, Aleksandra; Wąs, Marcin; Zozula, Natalia; Tomczewska, Zuzanna; Rykucka, Aleksandra; Kiełbasa, Justyna; Kowalczyk, Agata; Bil, Katarzyna; Ślesicka, Iga; Przestrzelska, Magda; Winiarska, Natalia (Quality in Sport, 2024)
Introduction and purpose: Rosacea is a chronic inflammatory dermatosis. It mainly affects the central parts of the face and manifests itself with redness, erythema, telangiectasia, and papulopustular lesions. The aim of the work is to review current rosacea therapy techniques, detailing aesthetic medicine treatments. Material and methods: In order to create the review, the PubMed and Scopus databases were searched in April and May 2024. The searches took place between April 24 and May 15, 2024 and consisted of a critical analysis of the acquired sources of knowledge. State of knowledge: The introduction of lasers to the market has revolutionized the therapy of rosacea and appropriately selected parameters and patient qualification for the treatment ensure therapeutic success. Botulinum toxin is a potent neurotoxin that blocks the release of acetylcholine from the presynaptic vesicle. Appropriate home care is an extremely important factor in maintaining the disease in the remission phase. Conclusion Among the possibilities of aesthetic medicine, rosacea therapy is definitely dominated by laser therapy. There are several lasers available on the market today, the most commonly used of which is IPL. Ablative lasers are used to treat a deformed nose caused by rhinophyma. Botulinum toxin is administered as an intradermal injection, thanks to which it reduces erythema and redness of the skin. After appropriate treatment by a dermatologist and aesthetic medicine doctor, well-selected home care plays a key role in maintaining the disease in the remission phase.